Dimethyl Itaconate Attenuates CFA-Induced Inflammatory Pain via the NLRP3/ IL-1β Signaling Pathway - Lin, Jiaqi; Ren, Jinxuan; Zhu, Bin; Dai, Yi; Gao, Dave Schwinn; Xia, Suyun; Cheng, Zhenzhen; Huang, Yangyuxin; Yu, Lina (Frontiers in Pharmacology, 2022)
Itaconate plays a prominent role in anti-inflammatory effects and has gradually been ushered as a promising drug candidate for treating inflammatory diseases. However, its significance and underlying mechanism for inflammatory pain remain unexplored. In the current work, we investigated the effects and mechanisms of Dimethyl Itaconate (DI, a derivative of itaconate) on Complete Freund's adjuvant (CFA)-induced inflammatory pain in a rodent model. Here, we demonstrated that DI significantly reduced mechanical allodynia and thermal hyperalgesia. The DI attenuated neuroinflammation was evident with the amelioration of infiltrative macrophages in peripheral sites of the hind paw and the dorsal root ganglion. Concurrently, DI hindered the central microglia activation in the spinal cord. Mechanistically, DI inhibited the expression of pro-inflammatory factors Interleukin (IL)-1β, Tumor Necrosis Factor alpha (TNF-α), while upregulated anti-inflammatory factor IL-10. The analgesic mechanism of DI is related to the downregulation of the Nod-like receptor protein 3 (NLRP3) inflammasome complex and IL-1β secretion. This study suggested possible novel evidence for prospective itaconate utilization in the management of inflammatory pain.